Premature ovarian insufficiency: a review on the role of oxidative stress and the application of antioxidants - Shi, Yu-Qian; Zhu, Xi-Ting; Zhang, Su-Na; Ma, Yi-Fu; Han, Yan-Hua; Jiang, Yue; Zhang, Yue-Hui (Frontiers in Endocrinology, 2023)
Normal levels of reactive oxygen species (ROS) play an important role in regulating follicular growth, angiogenesis and sex hormone synthesis in ovarian tissue.When the balance between ROS and antioxidants is disrupted, however, it can cause serious consequences of oxidative stress (OS), and the quantity and quality of oocytes will decline. Therefore, this review discusses the interrelationship between OS and premature ovarian insufficiency(POI), the potential mechanisms and the methods by which antioxidants can improve POI through controlling the level of OS. We found that OS can mediate changes in genetic materials, signal pathways, transcription factors and ovarian microenvironment, resulting in abnormal apoptosis of ovarian granulosa cells (GCs) and abnormal meiosis as well as decreased mitochondrial Deoxyribonucleic Acid(mtDNA) and other changes, thus accelerating the process of ovarian aging. However, antioxidants, mesenchymal stem cells (MSCs),, biological enzymes and other antioxidants can delay the disease process of POI by reducing the ROS level in vivo. Keywords: Oxidative stress; Aging and oocyte; Premature ovarian insufficiency; Antioxidant; Mitochondrial dysfunction;